2009
DOI: 10.1111/j.1365-3148.2009.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII in the treatment of non‐haemophilia patients: physician under‐reporting of thromboembolic adverse events

Abstract: The objective of this study was to determine if clinically important thromboembolic adverse events (TAEs) because of recombinant activated factor VII (rFVIIa) administration are being under-reported. rFVIIa is a potent haemostatic agent with a short half-life of 2.6 h that is increasingly used in 'off-label' situations. Retrospective review of 94 patients who received rFVIIa during 1 January 2003 to 30 June 2007 was carried out at a tertiary care centre. Sixty-nine patients, 32 females and 37 males, mean age 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…Although this risk is likely to be acceptable in life-threatening situations, clinicians often underestimate the risk of thrombotic events from factor products. 42 Thus, there is a need for DOAC reversal agents that do not directly interact with the native coagulation system.…”
Section: Reversal Of Doacs For Bleeding or Invasive Proceduresmentioning
confidence: 99%
“…Although this risk is likely to be acceptable in life-threatening situations, clinicians often underestimate the risk of thrombotic events from factor products. 42 Thus, there is a need for DOAC reversal agents that do not directly interact with the native coagulation system.…”
Section: Reversal Of Doacs For Bleeding or Invasive Proceduresmentioning
confidence: 99%
“…In practice, many such TAEs may go unreported. 37 TAEs associated with use of rFVIIa reported to the FDA Adverse Event Reporting System during the first 5 years the drug was available (1999 -2004) were reviewed and found to be associated predominantly with off-label usage (151 of 168 reports). 38 Arterial events were most common (54% of total), including thromboembolic stroke (21%), myocardial infarction (19%), and other arterial thromboses (14%).…”
Section: Rfviia Use In Spontaneous Ichmentioning
confidence: 99%
“…Several other studies have reported off-label use to similar degrees. 37,38,[45][46][47][48] We and others at our own institution recently completed a retrospective study of off-label rFVIIa usage patterns throughout the United States as part of a comparative effectiveness review for the Agency for Healthcare Research and Quality. 49 We found that, in 2008 (the most recent year of our analysis), 97% of inpatient uses of rFVIIa were off-label.…”
Section: Current Approaches To Guidelines For Use Of Rfviiamentioning
confidence: 99%
“…12,29 In a retrospective analysis of 69 patients who received rFVIIa for various off-label uses (i.e., non-hemophilia patients), 36 possible thromboembolic adverse events were identified in 29 patients, including 12 patients with events judged related to rFVIIa. 34 The mean rFVIIa dose was 8.2 mg (i.e., 117 mg/kg for a 70-kg person). On average, the events were identified 8.8 days after exposure to the drug.…”
Section: Warfarin Reversalmentioning
confidence: 99%
“…Some four-factor PCC products (e.g., Beriplex P/N; Octaplex; Cofact, Sanquin Blood Supply, Amsterdam) contain these proteins, and administering these four-factor PCC products (an approach referred to as balanced PCC therapy) could in theory reduce the risk for thromboembolic complications. 34,41 Interpreting laboratory test results. Falsely elevated aPTT values also may occur if a syringe is used to obtain the blood sample and there is a delay in transferring the sample to a collection tube containing citrate.…”
Section: Warfarin Reversalmentioning
confidence: 99%